Development Of Lead Free Copper Alloy Casting; Mechanical Properties, Castability and Machinability - Umeda Takateru (Balai Besar Logam dan Mesin, 2004)
The regulation for the lead discharge in the environment was strengthened, in Japan, the standards 0.01 mg/I or less has been in force from April 2003. In order to meet the new standard, two technologies for reduction of lead dissolution into the drinking water have been developed in Japan; substitution of lead free copper alloys for lead bearing bronze (JIS-CAC406) and introduction of surface treatment technology. This technological trend was shortly reviewed. For development of lead free copper alloy casting, mechanical properties, castability and machinability of various lead free alloy castings were examined. Trial alloys used were commercially available ones such as the lead free bronze containing Bi, the lead free bronze containing Bi-Se, the lead free bronze containing Bi-Sb and the lead free brass containing Si. Mechanical properties of alloys were dependent on the pouring temperature and castings thickness and were generally less than those of tin bronze castings (JIS-CAC406, Cu-5 wt% Sn-5 wt% Zn-5 wt% Pb). The machinability of the lead free bronze containing Bi and Se was better than that of the lead free bronze castings containing Bi and Bi-Sb. But was still 10 to 15 % less than that of JIS-CAC406. In a lead free alloy substituted by Bi, adjustment of tin, zinc and bismuth contents was attempted and in the Bi-Se system, the adequate adjustment, for bismuth and selenium contents and also for tin, zinc and bismuth contents, was attempted. New alloy in which the mechanical properties sufficiently satisfy the standard for JIS-CAC406 is developed.